Managing further rehabilitation in longer-term stroke patients in the community: A new approach - N.A Aziz,; A.A Raymond, (Penerbit UKM, 2008)
Stroke is becoming a major public health issue in our country due to the fact that there is an increasing life span of our population. Due to advancement of acute management of stroke, three out of four people will survive beyond the acute phase of stroke. Stroke care providers are still debating regarding the exact period of the terminology ‘longer-term stroke’; however many agreed that long-term of stroke refers to the period of one year and thereafter as this period is the determinant for longer-term survival. Management beyond the first year of stroke is complex, encompasses all aspects of patient’s life; physical, psychological and integration into community. Rehabilitation being the cornerstone of longer-term stroke management should now focused on more evidence-based approach as to be effective and relevant to the stroke patients